Five year study of prenatal testing for Huntington's disease: demand, attitudes, and psychological assessment. Issue 7 (July 1993) - Adam, S; Wiggins, S; Whyte, P; Bloch, M; Shokeir, M H; Soltan, H; Meschino, W; Summers, A; Suchowersky, O; Welch, J P
Abstract : Adult predictive and prenatal testing programmes for Huntington's disease (HD) in Canada have been available since 1986. However, the demand for prenatal testing and the reasons why some people choose not to have the prenatal test for this late onset disorder have not been well documented. In addition, the knowledge and attitudes of adult predictive testing candidates and their partners about prenatal testing are not well known nor are the psychological effects of prenatal testing well understood. As of September 1991, 425 subjects had entered the Canadian Collaborative Study of Predictive Testing and, of these, 47 subjects or their partners had become pregnant. Of this group, 14 (30%) couples requested prenatal testing, 24 (51%) couples did not want prenatal testing, and nine (19%) at risk subjects had already received a decreased risk through adult predictive testing and, therefore, were not eligible for the prenatal test. Of the 14 couples who initially requested prenatal testing, seven withdrew. Thus, demand for the prenatal test by eligible candidates was 7/38 or 18%, which is much lower than the 32 to 65% expected based on early survey data. The most frequently cited reason for declining prenatal testing was the hope that a cure would be found in time for their children. While the majority of adult predictive testing candidates (71%) in our study had accurate information about definitive prenatal testing, many (63%) did not have a correct understanding of exclusion prenatal testing. Although no serious adverse events such as suicide planning or admission to psychiatric hospital have occurred, a particular need for careful counselling was identified for those at risk candidates and their partners who have one prenatal test and feel compelled to use the test again in future pregnancies. Even though prenatal testing for HD is not requested as often originally expected, it still remains a desired option for some at risk persons and their partners.